The implied internal rate of return in conventional residual valuations of development sites. Issue 3 (3rd July 2018) - Crosby, Neil; Devaney, Steven; Wyatt, Peter
Abstract: Explicit discounted cash flow methods are used in many countries to assess the value of real estate investments or their likely rate of return given a particular price. These are typically supplemented by simpler models for the purpose of estimating market value, leading to debate about different approaches. A parallel situation exists in the case of UK development sites: both cash flow appraisals and simpler residual valuations are used to assess site values. Yet debate here has been limited, even though traditional residual valuations involve steps that depart from project appraisal practices used in mainstream capital budgeting. We explore the relationship between the profit and interest allowances used in traditional residual valuations and the internal rates of return that they appear to imply. Published residual valuations typically allow for profit through use of a simple proportionate relationship between required profit and the cost or final value of a scheme. They also show limited variation in their profit assumptions, but this implies large differences in expected IRRs. Simulated examples then illustrate the implications of applying standard profit-on-cost rates to schemes of different lengths and with different levels of land value. Findings for project duration, in particular, are noteworthy since they indicate that lower IRRs are implied for longer projects, though this relationship is not necessarily rational.